IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS PROYEK DALAM MENINGKATKAN KEMANDIRIAN BELAJAR SISWA - Oktaviana. N, Shella; Saputra, M. Indra (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2024)
Innovation in learning methods is essential to ensure that education runs well. Using suitable media, techniques, tools, and materials can make the learning process more attractive, practical, and fun for students. This study aims to determine how implementing the project-based learning model can increase students' learning independence in Islamic Religious Education subjects and identify the obstacles educators face in the process. The descriptive qualitative research method was chosen to provide a comprehensive picture. The subjects in this study are students and teachers of PAI grade VIII SMP Negeri 4 Bandar Lampung. Data was collected using interview, observation, and document study techniques. The data is then analyzed descriptively through the stages of data reduction, data presentation, and conclusions drawn. The study results show that applying the project-based learning model to the material on the introduction and understanding of believing in the prophet and messenger shows excellent potential in increasing students' learning independence. The project carried out in this learning is in the form of making works or other activities related to believing in the prophet and the messenger. With this approach, students not only develop skills in finding and processing information from various sources but can also apply religious values in daily life in a more meaningful way. The obstacles encountered in implementing the learning model are intensive time management and limited resources.